Systematic Equation-Based Design of a 10-Bit, 500-MS/s Single-Channel SAR A/D Converter With 2-GHz Resolution Bandwidth - Tetsuya Iizuka; Ritaro Takenaka; Hao Xu; Asad A. Abidi (IEEE Open Journal of the Solid-State Circuits Society)
A 10-b self-timed SAR A/D converter is designed in 28-nm FDSOI CMOS to convert at 500 MS/s. It maintains this effective number of bits across an input bandwidth of 2 GHz, because it will be used as one of eight identical converters in a time-interleaved system to reach a conversion rate of 4 GS/s. This circuit is based almost entirely on formal expressions for every building block circuit. This approach led to a strikingly short development time where every design choice was defensibly optimum and the prototype chip yielded near-textbook performance from the first silicon. The figure of merit is at the state of the art.